Link Between Umbilical Cord Blood Adipokines and Early Childhood Health - Ava M. Boyle; Olivia J. Holland; Deanne H. Hryciw (Endocrines)
Introduction: Early-life neurological and inflammatory disorders significantly affect long-term cognitive, social, and emotional development. The ‘Developmental Origins of Health and Disease’ hypothesis states that an adverse intrauterine environment may predispose offspring to chronic health conditions due to altered growth and development. Factors measured in umbilical cord blood can provide information about the status of the in utero environment during development. Evidence indicates that umbilical cord blood adipokines, namely leptin and adiponectin, may influence fetal programming and could be useful in predicting offspring health outcomes. Leptin and adiponectin are crucial in energy homeostasis, immune response, and placental function, and some studies suggest that altered concentrations may increase the risk of developing inflammatory and neurological disorders in later life. Further, limited studies have demonstrated sex-specific differences in adipokine concentrations and disease risk. Conclusions: Understanding the role of umbilical cord blood adipokines in fetal programming could offer new insights into early risk prediction and intervention strategies, promoting better health outcomes for children at risk of neurological and inflammatory diseases due to an adverse maternal environment during pregnancy.